Additive manufacturing of Ca–Mg silicate scaffolds supported by flame-synthesized glass microspheres. Issue 7 (1st April 2022) - Kraxner, J.; Elsayed, H.; Dasan, A.; Hujová, M.; Michálková, M.; Michálek, M.; Bernardo, E.; Galusek, D.
Abstract: Novel manufacturing techniques such as additive manufacturing also referred to as 3D printing hold a critical role in the preparation of novel bioactive three-dimensional glass-ceramic scaffolds. The present paper focuses on the use of Ca–Mg silicates microspheres (Ca2 MgSi2 O7, i.e. 40 mol% CaO, 20% MgO and 40% SiO2 ) for the fabrication of 3D structures by additive manufacturing. In the first step, the crystallization of the åkermanite system was avoided, by feeding nearly fully crystallized precursor powders prepared by conventional melt quenching into oxygen-methane (O2 /CH4 ) torch, and solid glass microspheres (SGMs) with diameters bellow 63 μm were prepared. In the second step, the crystallization was utilized to control the viscous flow of SGMs during firing of reticulated scaffolds, obtained by digital light processing (DLP) of the SGMs suspended in a photocurable acrylate binder. The spheroidal shape facilitated a high solid content, up to 77 wt% of the SGMs in the suspension. After burn-out of the organic binder, a fast sintering treatment at 950 °C, for 30 min, led to scaffolds preserving the macro-porosity from 3D printing model (diamond cell lattice) but with well densified struts. The crystallization of 3D scaffolds during the sintering process led to 3D structures with adequate strength-to-density ratio.